Evaluasi Usability Aplikasi SIAP TARIK Dengan Menggunakan Metode Usability Testing dan System Usability Scale (SUS) Pada Puskesmas Tarik Sidoarjo - Muhammad Ulul Albab Iryanto; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Puskesmas Tarik Kabupaten Sidoarjo is one of the community service institutions of Health that has 12 poly for its service. Total patients of Tarik are listed in approximately 15,000 people and have 82 doctors. The number of patients arriving per day averages as much as 100 to 250 people, so there is always a buildup of queues in the Puskesmas building and resulted in a decrease in the comfort of patients who come. The Puskesmas has therefore developed facility information about the Puskesmas Tarik and has the feature of booking queues in a mobile platform named SIAP TARIK. after 2 years of SIAP TARIK-use application of the Puskesmas Tarik Sidoarjo, Parties The Puskesmas receives feedback from its users. After analysis of the problem, researchers draw conclusions related to the usability of the system about the user's ease of the system. Therefore, summative testing is conducted on the system using usability testing methods and system usability scales by assigning tasks, filling questionnaires and conducting interviews. The results of usability testing and system usability scale indicate the level of usability SIAP TARIK is at the rating OK-good, grade "D" and is at the marginal high with the score SUS 66.5 that the results still need improvement to improve Its degree of mobility. With existing guidelines will be a reference in providing recommendations for the development of applications SIAP TARIK to forward.